The Novikov coalgebras - Kozybaev, Д.Х.; Naurazbekova, А.С. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2022)
: In the present paper, necessary and sufficient conditions are found under which a coalgebra is a left-symmetric coalgebra. A method for constructing coalgebras is described. An example of a left-symmetric coalgebra is constructed. Necessary and sufficient conditions are given under which a left-symmetric coalgebra is a Novikov coalgebra. An example of a non-locally finite Novikov coalgebra is constructed.